Pipe Stress and Turbine Nozzle Load Analysis for HP Steam Inlet and MP Steam Extraction on Turbine Generator 51G201T Capacity 10MW - Komarudin, Udin; Philo, Nia Nuraeni, Iftika; Syifa Puspani, Nissa (International Journal of Engineering and Technology, 2018)
Thermal pipe expansion on the turbine greatly affects the performance of the turbine, mainly produces misalignment in turbines. The stress analysis on the pipe and the load on the nozzle is very important to ensure that the stress that occurs is still safe and the load that occurs on the nozzle is still below the allowable load. Field information is known, Steam type of 51-G-201-T, capacity 10 MW, total weighs 58 tons, weight casing 37 tons, which has been operating since July 1989, has been occur misalignment on turbines. Stress pipe and load analysis of turbine nozzles on the turbine using software (Autopipe V8i Select Series 3 Edition by Bentley). In this perspective, calculation methodologies were developed in order to do quick analysis of the most common configurations, according to the codes ASME B31.1 (Piping Power). The results of the pipe stress analysis showed that the maximum sustained stress ratio occurred at point A39 (0.32), maximum displacement stress ratio at point A39 (0.97) and maximum hoop stress ratio at point A09 (0.44), all values below 1. This shows that the stress is still safe. The result of load analysis on the turbine casing is the direction x = -880 kg, y = 6246.4kg, z = -3697.7kg, smaller than the weight of the 37 tones turbine casing, so misalignment is not caused by shifting the turbine casing.Â Â